(untitled) (Rajshahi University Journal of Life & Earth and Agricultural Sciences, 2015)
A rapid and efficient protocol is outlined for in vitro propagation of muskmelon (Cucumis melo L.) Shoot tips, nodal segments and cotyledonary nodes from in vitro grown seedlings were used as explants. The explants were inoculated on MS medium fortified with different combinations and concentrations of growth regulators viz., BAP, NAA, GA3 and IBA for multiple shoot regeneration. Effective result was found on MS medium supplemented with 2.0 mg/l BAP, in which 90% and 70% cultures induced multiple shoots from nodal segments and shoot tip explants, respectively. Whereas, 70% cultures of cotyledonary nodes were found to induced shoots on MS medium with 1.5 mg/l BAP + 0.1 mg/l GA3. In vitro regenerated shoots were subcultured on half strength MS medium supplemented with different concentrations of IBA and NAA for successful root induction and the effective result (up to 70%) was found in medium with 1 mg/l IBA. Well rooted in vitro grown plantlets were acclimatized in sandy soil, where as 70% plantlets survived